Plant recovery techniques do not ensure biological soil‐crust recovery after gypsum quarrying: a call for active restoration. (10th November 2019) - Lorite, Juan; Agea, Daniel; García‐Robles, Helena; Cañadas, Eva M.; Rams, Susana; Sánchez‐Castillo, Pedro
Abstract : Biological soil crusts (biocrusts) are a key component of dryland ecosystems worldwide. However, large extensions of biocrusts are disturbed by human activities, gypsum quarry being an outstanding example. Restoration techniques applied have offered satisfactory results for vascular plants but they could greatly differ in promoting biocrust recovery. A basic question remains unaddressed: can measures for plant recovery accelerate or promote the recovery of biological crusts? We have examined eight different situations: undisturbed natural habitat, five treatments with no restoration measures (overgrazed area, abandoned quarry, topsoil removal from natural habitat, and two areas filled with gypsum mining spoil), and 2 areas receiving restoration measures (manual sowing and hydroseeding). We took 40 soil cores to determine cover of lichen, moss, and cyanobacteria. Biocrust richness and cover were higher in the undisturbed habitat, with remarkable differences for the different components among treatments. Cyanobacteria were well represented in all the cores (restored and non‐restored). Mosses were promoted the most by hydroseeding. Lichen cover was remarkably higher in undisturbed samples, very low in the quarry abandoned in 1992, and 0 in the rest. Complete spontaneous recovery of biocrusts was inefficient in the 25‐year period examined. Plant restoration measures could speed up its recovery comparing with non‐restored areas. Cyanobacteria and mosses can spontaneously recover fairly well. However, promoting them would accelerate the appearance of lichen. For lichen, inoculation or translocation of lichen thalli might be proposed. Therefore, our results call for the inclusion of active restoration measures of biocrust components in recovery plans, especially for lichens.